Possible Mechanism of Improving Neurodegenerative Diseases via Rejuvenation of Mitochondrial Function by Intermittent Fasting - WANG Fangfang, CUI Yanru, LI Jiayu, PANG Rizhao, ZHANG Anren (Zhongguo quanke yixue, 2023)
Age-related neurodegenerative diseases is increasing with the aggravation of global aging. Studies show that neurodegenerative diseases could be prevented or delayed by intermittent fasting (IF) regulating metabolic pathways, and the mechanism of action may be associated with improved mitochondrial function and metabolic homeostasis by IF. Mitochondrial dysfunction is an early marker of brain aging and neurodegeneration. These suggest that IF, mitochondria, and neurodegenerative diseases may be closely correlated. We reviewed the improvement effects of IF on neurodegenerative diseases, the important role of mitochondria in neurodegenerative diseases, the regulation of IF on mitochondrial function, and the effects of excessive calorie intake on neurons and mitochondrial function, and summarized that IF could improve mitochondrial function, while excessive calorie intake could damage the neurons and mitochondrial function. Future research could continue to focus on the mechanism of action and metabolism signal pathway of IF improving neurodegenerative diseases, which may be favorable to the determination of the proper window period for intervention, and the development of alternative targeted drug therapy, thereby assisting clinical application of IF.